Transient Mesenteric Ischemia Leads to Remodeling of Rat Mesenteric Resistance Arteries - Caracuel, Laura; Jiménez-Altayó, Francesc; Romo, Monica; Márquez, Ana; Dantas, Ana P.; Vila, Elisabet (Frontiers in Physiology, 2012)
Mesenteric ischemia/reperfusion (I/R) is associated with high rates of morbidity and mortality. We studied the effect of mesenteric I/R on structural and mechanical properties of rat mesenteric resistance artery (MRA) that, once disrupted, might impact the outcome of this devastating clinical condition. Superior mesenteric artery from Wistar-Kyoto rats was occluded (90 min) and reperfused (24 h). The effect of tezosentan, a dual endothelin (ET)-receptor antagonist, was studied in ischemic (IO) and sham-operated (SO) animals. MRA structure and mechanics were assessed by pressure myography. Nuclei distribution, elastin content and organization, collagen I/III and ET-1 expression, ET-1 plasma levels, superoxide anion (O2.-) production and mRNA levels of NAD(P)H-oxidase subunits were measured. To assess ET-1 effects on O2.- production, MRA from non-operated rats were incubated in culture medium with ET-1. Mesenteric I/R increased MRA wall thickness (P<0.05) and cross sectional area (P<0.05) but decreased wall stiffness (P<0.05). Arterial remodeling was paralleled by enhancement of: i) collagen I/III (P<0.01), ET-1 expression (P<0.05), and O2.- formation (P<0.01) in the vessel wall; ii) number of internal elastic lamina fenestrae (P<0.05) and iii) plasma levels of ET-1 (P<0.05). Moreover, ET-1 increased O2.- (P<0.05) production in cultured MRA. Tezosentan prevented hypertrophic remodeling and collagen I/III deposition, and enhanced O2.- production, but it did not affect the decreased wall stiffness after mesenteric I/R. These results indicate that 90 min occlusion/24 h reperfusion induces hypertrophic remodeling of MRA linked to ET-1-mediated increase of collagen and O2.-. Decreased stiffness may be associated with increased number of internal elastic lamina fenestrae. The resulting MRA remodeling, initially adaptive, might become maladaptive contributing to the pathology and poor outcome of mesenteric I/R, and might be a valuable treatment target for mesenteric I/R.